Synergy of Physical, Mental, Financial, and Environmental Health in Support of Sustainable Development Goals (SDGS) - Bayu PASUPATI; Putu Ayu Sita LAKSMI (Akuntansi dan Humaniora: Jurnal Pengabdian Masyarakat, 2025)
The 2025 Community Service Program – Community Empowerment by Warmadewa University Students (KKN-PMM) in Belantih Village, Kintamani District, Bangli Regency, was held for one month with the theme "Synergy of Physical, Mental, Financial, and Environmental Health in Supporting the Sustainable Development Goals (SDGs)." Involving 25 students from various disciplines, this program was designed to address multidimensional problems identified through village situation analysis, including low mental health literacy, suboptimal waste management, limited diversification of locally based economic products (coffee and oranges), low financial literacy, and challenges in basic education (reading, writing, and arithmetic). Implementation methods included direct education, participatory training, ongoing mentoring, and cooperation activities. The program results showed a significant increase in community understanding of mental health, the application of the 3R principle (Reduce, Reuse, Recycle), innovative product processing skills (coffee cake and orange wine), the ability to manage household finances, and children's learning progress. This program directly contributes to the achievement of several SDGs, such as SDG 3 (Health and Well-Being), SDG 4 (Quality Education), SDG 5 (Gender Equality), SDG 8 (Decent Work and Economic Growth), SDG 12 (Responsible Consumption and Production), and SDG 13 (Addressing Climate Change). The program's success is supported by close collaboration between students, village officials, educational institutions, and the community. This article concludes that a holistic and locally based approach is key to successful community empowerment. It is recommended that the village government and universities continue their partnership to ensure the program's sustainability.